Analisis Manajemen Humas Dalam Menjalankan Fungsi Kontrol Sosial Istana Kedatuan Luwu Di Masyarakat - Firman Patawari; Ajar Muthia; Safitriyani Safitriyani (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to find out how public relations management the Kedatuan Luwu Palace performs its function as social control in society. This study is a field research using descriptive qualitative method. The author used the methods of interview, observation, literature study and literature. The results of this study show that: First, there is a good relationship between the Palace of Kedatuan Luwu and the local community. Second, the systematics in resolving conflicts that occur specifically in the Kedatuan Luwu area are based on the division of tasks and duties that have been carried out well so far.